Can Lp(a) become the next A1C? A case for digital health management tools to overcome inertia to Lipoprotein (a) testing - Wedemeyer, Christof; Peters, Martin; Jones, Graham (Frontiers in Cardiovascular Medicine, 2025)
Despite its known correlations with risk of cardiovascular disease, awareness and testing for Lipoprotein (a) lags that of other serological markers with estimates that less than 1% of the US population have undergone screening. Herein we outline how digital tools framed around motivational models (COM-B and SEM), might help increase likelihood of patients seeking Lp(a) testing as part of their managed care. Furthermore, we highlight how recent trends in prescription of GLP-1 receptor antagonists are serving to motivate patients to manage biomarkers related to T2D and obesity, which are also relevant in cardiovascular disease. Capitalizing on this trend to stimulate interest in Lp(a) management could have near term consequence, and with disease modifying therapies in development ultimately improve outcomes in cardiovascular disease.